Limited Clinical Utility of Chest Radiography in Asymptomatic Patients after Interventional Radiology-Performed Ultrasound-Guided Thoracentesis: Analysis of 3,022 Consecutive Patients - Bundy, Jacob J.; Hage, Anthony N.; Jairath, Ruple; Jiao, Albert; Wadhwa, Vibhor; Gutta, Narendra B.; Srinivasa, Ravi N.; Gemmete, Joseph J.; Monroe, Eric J.; Chick, Jeffrey Forris Beecham (Journal of Clinical Interventional Radiology ISVIR, 2021)
Purpose The aim of this study was to report the utility of chest radiography following interventional radiology-performed ultrasound-guided thoracentesis.Materials and Methods A total of 3,998 patients underwent thoracentesis between 2003 and 2018 at two institutions. A total of 3,022 (75.6%) patients were older than 18 years old, underwent interventional radiology-performed ultrasound-guided thoracentesis, and had same-day post-procedure chest radiograph evaluation. Patient age (years), laterality of thoracentesis, procedural technical success, volume of fluid removed (mL), method of post-procedure chest imaging, absence or presence of pneumothorax, pneumothorax size (mm), pneumothorax management measures, and clinical outcomes were recorded. Technical success was defined as successful aspiration of pleural fluid. Post-procedure clinical outcomes included new patient-perceived dyspnea and hypoxia (oxygen saturations < 90% on room air). Costs associated with radiographs were estimated using Medicare and Medicaid fee schedules.Results Mean age was 56.7 ± 15.5 years. Interventional radiology-performed ultrasound-guided thoracentesis was performed on the left (n = 1,531; 50.7%), right (n = 1,477; 48.9%), and bilaterally (n = 14; 0.5%) using 5-French catheters. Technical success was 100% (n = 3,022). Mean volume of 940 ± 550 mL of fluid was removed. Post-procedure imaging was performed in the form of posteroanterior (PA) (2.6%; 78/3,022), anteroposterior (AP) (17.0%; 513/3,022), PA and lateral (77.9%; 2,355/3,022), or PA, lateral, and left lateral decubitus (2.5%; 76/3,022) chest radiographs. Post-procedural pneumothorax was identified in 21 (0.69%) patients. Mean pneumothorax size, measured on chest radiograph as the longest distance from the chest wall to the lung, was 18.8 ± 10.2 mm (range: 5.0–35.0 mm). Of the 21 pneumothoraces, 7 (33.3%) were asymptomatic, resolved spontaneously, and had a mean size of 6.4 ± 2.4 mm. Fourteen pneumothoraces, of mean size 25.0 ± 5.8 mm, required management with a pleural drainage catheter (66.6%). The overall incidence of pneumothorax requiring pleural drainage catheter placement following interventional radiology-performed ultrasound-guided thoracentesis was 0.46% (14/3,022). Of the patients requiring drainage catheter placement, 12/14 (85.7%) and 13/14 (92.9%) had dyspnea and hypoxia, respectively. Potential costs to Medicare and Medicaid, for chest radiographs, in this study, were $27,547 and $10,581, respectively.Conclusion The incidence of clinically significant pneumothorax requiring catheter drainage following interventional radiology-operated ultrasound-guided thoracentesis is exceedingly low (0.46%), and routine post-procedure chest radiographs in asymptomatic patients provide little value. Reserving post-procedure chest radiographs for patients with post-procedure dyspnea or hypoxia will result in more efficient resource utilization and health care cost savings.
Keywords: ultrasound; thoracentesis; pneumothorax; chest radiograph; chest tube placement; drainage catheter placement; interventional radiology